2005
DOI: 10.1002/jcla.20057
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of oxidation enzyme eNOS and myeloperoxidase in primary open angle glaucoma

Abstract: Genetic factors and the influence of superoxide are known to play roles in the etiology of glaucoma. We evaluated the association between primary open angle glaucoma (POAG) and two polymorphisms in the epithelial nitric oxide synthase (eNOS) gene, and one polymorphism in the myeloperoxidase (MPO) gene. We enrolled 66 patients with POAG and 100 healthy volunteers in this study. The polymorphisms in the eNOS and the polymorphism MPO -463 G-to-A in the MPO gene were resolved by polymorphism polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…In the overall analysis, we observed a marginal difference in the frequency of this polymorphism among cases and controls, which was not significant after adjustments for other variables of interest. These results are in accordance with the findings observed by other authors (Fan et al, 2010;Lin et al, 2005;Logan et al, 2005). The Glu298Asp polymorphism, in turn, has been associated with risk of ischemic shock (Berger et al, 2007), coronary spasm (Yoshimura et al, 1998), coronary artery disease (Colombo et al, 2003;Hingorani et al, 1999), myocardial infarction (Hibi et al, 1998;Shimasaki et al, 1998) and NAION (Sakai et al, 2007).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the overall analysis, we observed a marginal difference in the frequency of this polymorphism among cases and controls, which was not significant after adjustments for other variables of interest. These results are in accordance with the findings observed by other authors (Fan et al, 2010;Lin et al, 2005;Logan et al, 2005). The Glu298Asp polymorphism, in turn, has been associated with risk of ischemic shock (Berger et al, 2007), coronary spasm (Yoshimura et al, 1998), coronary artery disease (Colombo et al, 2003;Hingorani et al, 1999), myocardial infarction (Hibi et al, 1998;Shimasaki et al, 1998) and NAION (Sakai et al, 2007).…”
Section: Discussionsupporting
confidence: 94%
“…While some studies have implicated polymorphisms in the promoter region or inside the eNOS in the risk of POAG (Ayub et al, 2010;Liao et al, 2011;Tunny et al, 1998), other authors found no significant association (Fan et al, 2010;Lin et al, 2005;Logan et al, 2005). Interestingly, recent reports indicate that these different polymorphisms could interact with other exposure factors in modulating the risk of POAG, such as gender, use of postmenopausal hormones (PMHs), hypertension and smoking (Kang et al, 2010(Kang et al, , 2011.…”
Section: Introductionmentioning
confidence: 92%
“…28 However, another promoter SNP (rs2070744) of NOS3 was not associated with POAG in two other studies. 69,70 In addition, the 27-bp repeat alleles in intron 4 of NOS3 were associated with POAG in British and Pakistani populations 70,71 but not in a Chinese population. 69 In the present study, we did not find any association between two NOS3 SNPs (rs2070744 and rs1799983) and POAG.…”
Section: Discussionmentioning
confidence: 99%
“…69,70 In addition, the 27-bp repeat alleles in intron 4 of NOS3 were associated with POAG in British and Pakistani populations 70,71 but not in a Chinese population. 69 In the present study, we did not find any association between two NOS3 SNPs (rs2070744 and rs1799983) and POAG. Of note, the minor allele T of rs3918226 in NOS3 was not found in our Chinese sample (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…A part of this problem is that molecular pathways have been used to work backwards to a genetic predisposition. As in the case of nitric oxide synthase 3 (NOS3) , different expression patterns were found in the aqueous humour of glaucomatous patients compared with matched patients 122,123 . However, when nucleotide polymorphisms that had been proven to be functionally important in the NOS3 gene were investigated, conflicting results were obtained 122,123 .…”
Section: Poagandgeneticassociationstudiesmentioning
confidence: 99%